Correction: Motor variability during resistance training: Acceleration signal as intensity indicator. - Miguel López-Fernández; Fernando García-Aguilar; Pablo Asencio; Carla Caballero; Francisco J Moreno; Rafael Sabido (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0307949.].